Keefektifan Pembelajaran Dengan Sumber Belajar Interaktif Berbasis Komputer Ditinjau Dari Motivasi Dan Prestasi Belajar Matematika - Satriawan Satriawan; Dhoriva Urwatul Wutsqa (PYTHAGORAS Jurnal Pendidikan Matematika, 2013)
Penelitian ini bertujuan untuk: (1) mendeskripsikan keefektifan pembelajaran dengan sumber belajar interaktif berbasis komputer (SBIBK) dan pembelajaran dengan buku sekolah elektronik (BSE); (2) Mengetahui apakah pembelajaran dengan SBIBK lebih efektif dibandingkan pembelajaran dengan BSE ditinjau dari motivasi dan prestasi belajar matematika. Populasi penelitian ini seluruh siswa kelas XI SMK Negeri 1 Alas, Kab. Sumbawa. Sampel ditentukan secara acak, yaitu kelas XI Multimedia menggunakan SBIBK, sedangkan XI Tekhnik Komputer Jaringan menggunakan BSE. Instrumen yang digunakan adalah angket motivasi dan tes prestasi belajar matematika. Uji keefektifan pembelajaran menggunakan one sample t test. Untuk mengetahui pembelajaran yang lebih efektif, digunakan uji independent samples t test dengan kriteria bonferroni. Hasil penelitian ini adalah: (1) pembelajaran dengan SBIBK efektif ditinjau dari motivasi dan prestasi belajar matematika; (2) pembelajaran dengan BSE efektif ditinjau dari prestasi belajar matematika, namun tidak efektif ditinjau dari motivasi belajar matematika; (3) Pembelajaran dengan SBIBK lebih efektif dibandingkan pembelajaran dengan BSE.Kata Kunci: pembelajaran, sumber belajar interaktif berbasis komputer, buku sekolah elektronik, motivasi, prestasi belajar matematika The Effectiveness of the Instruction with Computer-Based Interactive Learning Resources in Terms of Motivation and Mathematics Achievement AbstractThis study aims to describe: (1) the effectiveness of the instruction with computer-based interactive learning resources (CBILR) and the instruction with electronic textbooks (ETb), in terms of students’ motivation to learn mathematics and mathematics achievement; (2) whether the instruction with CBILR is more effective than instruction with ETb in terms of students’ motivation to learn mathematics and mathematics achievement.The research population comprised all Year XI students, consisting of nine classes of SMK Negeri 1 Alas Sumbawa. From the population, two classes, Class XI Multimedia (MM) and Class XI Computer Network Technology (CNT), were established as the research sample randomly. Class XI MM learned with the CBILR and Class XI CNT learned with ETb. The data collecting instruments consisted of questionnaires for students’ motivation to learn mathematics and a learning mathematics achievement test. To test the effectiveness of the instruction with CBLIR and instruction with ETb, the data were analyzed using the one sample t-test. The data were analyzed using the independent sample t tests with the bonferroni test criteria to determine the more effective learning resources.The results are as follows: (1) the instruction with CBILR is effective in terms of motivation and mathematics achievement; (2) the instruction with ETb is effective in terms of mathematics achievement, but it is not effective in terms of motivation to learn mathematics. (3) The instruction with computer-based interactive learning resources is more effective than instruction with electronic textbooks.Keywords: instruction, computer-based interactive learning resources, electronic textbooks, motiva-tion, learning mathematics achievement